'Four Times Love' and the making of the Nordic welfare state. Issue 2 (1st June 2019) - Laine, Kimmo
This article focuses on 'Four Times Love' (Faustman and Jacobsen, 1951), the first feature film produced by companies from four Nordic countries. As a transauthoral omnibus film, credited to two directors and several independently working scriptwriters, 'Four Times Love' has a reputation as an incoherent film. Indeed, the project started with only a relatively vague idea of a Swedish frame story and one protagonist connecting three episodes that take place in Finland, Denmark and Norway. As the script evolved, however, unifying themes central to the Nordic welfare state ‐ concerning, for example, social equality and political neutrality ‐ seem to have gained ground. The aim of this article is to read this film as a manifestation of such complementary ideas and ideals surrounding the then (re-)emerging Nordic welfare state system.